1981
DOI: 10.1104/pp.67.1.143
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Morphological Constraints on Transport in Nodules

Abstract: MATERIALS AND METHODS Estimation of Flows. We will approach the quantification of the flows from a realistic agronomic goal of a nitrogen fixation rate of 2 kg N ha-' day-' (13). We will consider a soybean crop with a plant population of 2 x 105 plants ha-' and with 100 nodules/ plant. Each nodule then will be assumed to fix nitrogen at a rate of about 1 x 10-9 g N s-'. This number will be used to estimate first the required flow of glucose and then of 02.Glucose is required in the nitrogen fixation process as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
44
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 13 publications
3
44
1
Order By: Relevance
“…The mathematical model of Sinclair and Goudriaan (21) established that a layer of water on the order of 50 ,m thick would provide a diffusion resistance consistent with experimental data. The actual baffler is presumably more complex, with 02 diffusion both through cells and through intercellular spaces filled with air or water.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…The mathematical model of Sinclair and Goudriaan (21) established that a layer of water on the order of 50 ,m thick would provide a diffusion resistance consistent with experimental data. The actual baffler is presumably more complex, with 02 diffusion both through cells and through intercellular spaces filled with air or water.…”
mentioning
confidence: 60%
“…The unsteady-state 02 method for determining nodule permeability was tested using data generated by the model. The accuracy of the method was confirmed, provided that certain assumptions (full oxygenation of leghemoglobin under pure 02 and uniform conditions in the nodule interior) are met.A diffusion barrier in legume root nodules restricts 02 flux into the nodule and thereby protects nitrogenase from inactivation by 02 (21,22). The responses of nodules to such seemingly unrelated factors as drought, nitrate, and defoliation all apparently involve changes in the gas permeability of this barrier (8,10,14,17,23,24 Variable gas permeability of nodules might result from changes in (a) the number or size of gas-filled radial pores through the barrier, (b) the thickness of water plugs in radial pores, (c) the extent of flooding between layers of cells, or (d) flooding of airspaces in the central zone.…”
mentioning
confidence: 99%
“…Drought stress decreases nitrogen fixation rates as measured by both acetylene reduction (1,7,(17)(18)(19)(20)(21)(22) and 'sN uptake (16). While some researchers have concluded that this loss of nodule activity is due to an inhibition ofphotosynthesis (8,9,13), Sprent (22) concluded that nitrogen fixation is more sensitive than photosynthesis to drought stress.…”
mentioning
confidence: 99%
“…They presumed that the depressed oxygen uptake was caused by either a loss ofoxygen conductance through the nodule or by inhibition of oxygen requiring reactions, or perhaps by both. Restricted oxygen conductance has been shown by theoretical arguments to be an important feature of viable, well-watered nodules (16).…”
mentioning
confidence: 99%
“…Similar permeability changes occur in response to acetylene exposure (12) or with increased or decreased external 02 concentration (23,27). Studies with microelectrodes (19,27) and theoretical considerations (18) suggest that nodule permeability is limited mainly by one or more layers of tightly packed cells in the nodule cortex.…”
mentioning
confidence: 99%